The Suitability of Compatibility Test Results with Gel Method between Diagnostic Grifols Gel Coombs and Diamed-Identification - Tigor Pandapotan Sianturi; Betty Agustina Tambunan (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2020)
A compatibility test as part of a pre-transfusion test is mandatory to ensure blood compatibility between patients anddonors. Diamed-ID as the first gel-based product is commonly used as a reference for the compatibility test. The presence ofnew products such as DG Gel Coombs encourages research to compare them with reference methods. This study aimed toanalyze the suitability of DG Gel Coombs to Diamed-ID in the compatibility test with the same sample. This cross-sectionalanalytic observational study was conducted during November 2017-February 2018 at the Blood Transfusion Unit Dr.Soetomo Hospital, Surabaya using blood samples (n=40), which met the inclusion and exclusion criteria. Simultaneoustesting of the two products was according to the manufacturing requirements of each product (using different LISS reagentsfor red blood cell suspensions and centrifugation arrangements). The suitability of results was tested with Cohen's kappaand significant differences with McNemar. There was a minimum suitability of DG Gel Coombs to Diamed-ID for majorcompatibility tests, κ 0.307 (95% CI: -0.029-0.643), significance 0.007 (p < 0.05) and moderate for minor, κ 0,678 (95% CI:0.454-0.903), significance <0.0001 (p < 0.05). McNemar's significance was 0.016 (p < 0.05) for major compatibility test and0.031 (p < 0.05) for minor. Referring to Diamed-ID's results, false negatives were found on DG Gel Coombs for majorcompatibility tests (n=7) and minor (n=6). The suitability of results from DG Gel Coombs and Diamed-ID is not strong forcompatibility testing.